Gender Differences in EFL Coursebook Used in Islamic School of Bengkulu Province - Hadianto, Arief (Journal of English for Specific Purposes in Indonesia, 2022)
This study aims to see if there is a gender bias in the English textbooks for EFL used by Islamic schools in Bengkulu province. The objects of the research used are the course books used in Islamic schools in Bengkulu city, entitled "Bright an English 2 curriculum 2013 revisi" and "Grow with English 5 (a thematic English for elementary schools)" published by Erlangga. This study was analyzed based on six aspects according to Logsdon, namely: (1) the total number of male/female photos, (2) the total number of male/female noted, (3) the total number of male/female actors, (4) overall amount of male/female gameplay, (5) total number of male/female role models, and (6) structure of citing male/female names. The result showed that there is gender bias in the course books Bright an English 2 and Grow with English 5. Males are dominant in the Bright an English 2 book as a whole in categories 1,2,3,4, and 6, but not in the Grow with English book. In the book Grow with English, women are dominant in the first and second categories. Finally, the dominant gender bias lies in men. However, there are similarities in the comparison of gender differences between the two books in the fifth category, namely the total of male/female role models